Assessment of dietary adequacy for important brain micronutrients in patients presenting to a traumatic brain injury clinic for evaluation. (November 2014) - Wahls, Terry; Rubenstein, Linda; Hall, Michael; Snetselaar, Linda
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To evaluate dietary adequacy of patients presenting for evaluation at an outpatient traumatic brain injury (TBI) clinic. Methods We identified 14 key micronutrients with defined dietary intake reference ranges that are considered important for brain health. Adult patients completed the Brief NutritionQuest Food Frequency Questionnaire (FFQ) to calculate estimated nutrient intake. Medical records were abstracted for diagnoses, body mass index, and neurobehavioral subscale scores. Nutrients were assessed individually and were also summarized into a summary score. Associations between individual nutrients, summary nutrient intake, and neurobehavioral scores were assessed. Results A total of 39 FFQs were completed by subjects, and 25 (64%) had recorded neurobehavioral scores. No subjects met the recommended dietary allowances (RDAs) for all 14 micronutrients. Ten (26%) met the RDAs for 6 or fewer nutrients, and 10 met the RDAs for 11–12 nutrients. Of 12 nutrients with sufficient sample size for analysis, 11 (92%) were associated with worse mean somatic scores, 9 (75%) were associated with worse cognitive scores, and 8 (67%) were linked with worse affective scores for those with the lowest nutrient intake compared with those who had the highest intake. However, only four nutrients were statistically associated with the somatic mean score: folate (P = 0.010), magnesium (P = 0.082), vitamin C (P = 0.021), and vitamin K (P = 0.024). None were linked with cognitive or affective scores. Discussion Diets failing to meet RDAs for important brain nutrients were common in an outpatient TBI clinic, with the worst mean neurobehavioral scores for those patients not meeting the estimated average requirements.